The Development of Assessment Instruments Skills of Cultural Lesson Arts and Workshops in Primary School Based on Mobile - Rahmawati, Laili; Utomo, Udi; Ahmadi, Farid (Universitas Negeri Semarang, 2018)
The current instruments can not be used to assess the students' skills on the subjects of culture arts and the workshops in particular the material of collage in Primary School objectively. This research aims to develop instruments assessment skills on the subjects of culture arts and the workshops in Primary School based mobile valid, reliable, and effective. This researches method using R & D model of ADDIE with stages Analyze, Design, Develop, Implement, Evaluate. The sample of this study was 75 students. The results show the validity of the contents of 10 criteria measured values> 0.3, which means the instrument valid instrument developed skills. Results of Kaiser Meyer Olkin (KMO) 0.852 and Bartlett's with 0.000 significances, anti image correlation shows that the correlation value between the criteria measured to get correlation value > 0.5 therefore all the criteria measured can be in factor analysis by including all items. Exploratory factor analysis showed 3 factors formed from 10 criteria measured. The loading factor values for each criterion measured at each factor is> 0.3. Based on Alpha Cronbach's reliability test obtained value of 0.847, the instrument is declared reliable. The conclusions show the instrument of skill assessment on the subjects of culture arts and workshops in particular collage material in mobile based Primary School, reliable and effective use. The benefits derived from the research of the assessment instrument developed can be used as teacher guidance in the Primary School in conducting assessment of skills on the learning of cultural arts and workshops.